"With This You Can Meet Your Baby": Fetal Personhood and Audible Heartbeats in Oaxacan Public Health. (1st June 2016) - Howes‐Mischel, Rebecca
Abstract : This article examines how amplified fetal heartbeats may be used to make claims about fetuses' social presence. These claims are supported by the Mexican Public Health system's selection of the maternal–child relationship as a key site of clinical intervention, intertwining medical and moral discourses. Drawing on the robust literature on cross‐cultural propositions of "fetal personhood, " this analysis uses ethnographic material from public health institutions in Oaxaca, Mexico, to explore how doctors use diagnostic technology to materialize fetuses for their patients. I argue that Spanish's epistemological distinction between saber (to have knowledge about) and conocer (to be acquainted with) is key to how diagnostic technologies may be deployed to make social claims. I use one doctor's attempts to use technology to shift her patient from saber to conocer as illustrative of underlying cultural logics about fetal embodiment and its proof. Focused on the under‐theorized socio–medical deployment of audio fetal heartbeat technology, this article suggests that sound—in addition to sight—is a potent tool for constructing fetal personhood.